Neuro-Cognitive Architectures of Early and Adult Language Processing: The Role of Multisensory Integration in Overcoming Learning Barriers (American Innovator: Journal of Emerging Technologies and Research, 2026)
Language learning difficulties among adult learners are frequently interpreted as evidence of reduced cognitive ability, declining memory capacity, or age-related limitations. However, contemporary research in cognitive neuroscience suggests that successful learning depends not only on learners’ cognitive resources but also on the interaction between instructional approaches and the mechanisms through which the brain processes, organizes, and retrieves information. This article examines the role of multisensory integration and embodied learning in supporting English language acquisition among adult learners. The study is based on a classroom intervention involving 20 English learners aged 30–50 who experienced persistent difficulties in memorizing irregular verb forms through conventional approaches, including translation, explicit explanation, audiovisual materials, and repetition activities. Following the implementation of a multisensory approach involving gestures, physical movement, and oral drilling, learners demonstrated improved recall of irregular verb forms. A notable observation was that learners spontaneously reproduced associated gestures when experiencing retrieval difficulties, suggesting that motor actions functioned as cognitive retrieval cues.
Keywords: neuro-cognitive architecture; multisensory integration; embodied cognition